Recent Development on HIV Variants and HIV Vaccine - Ridwan Balatif; Fadlan Hafizh Harahap; Isni Dhiyah Almira (Cermin Dunia Kedokteran, 2022)
Human immunodeficiency virus (HIV) is a virus from the Retrovirus family that attacks human immune cells, especially T lymphocytes. The increasing number of HIV cases requires a more effective preventive measure; among others is through vaccination. Although it has been about 40 years, there is no HIV vaccine on the market yet. It can be because of many variations of HIV and each country has its own dominant HIV variant. In addition, the ability of HIV virus to evade immune responses, high mutation rates, and limited experimental animals add to the difficulties to develop effective vaccines. As of May 2022, 16 vaccines are currently undergoing phase I/II clinical trials. Among HIV vaccines that have already undergone phase III clinical trials, only RV 144 vaccine gave promising results, with efficacy reaching 31.2%. The development of the HIV vaccine continues to obtain a safe and effective HIV vaccine. Human immunodeficiency virus (HIV) merupakan virus dari famili Retrovirus yang menyerang sel imun manusia terutama limfosit T. Kasus infeksi HIV yang terus meningkat, membutuhkan tindakan pencegahan yang lebih efektif antara lain dengan vaksin HIV. Tetapi, meskipun sudah sekitar 40 tahun, belum ada vaksin HIV yang diedarkan. Hal ini bisa karena banyaknya variasi HIV serta tiap negara memiliki varian HIV dominan yang berbeda. Selain itu, kemampuan HIV menghindari respon imun, laju mutasi yang tinggi, ditambah dengan keterbatasan hewan coba, menyulitkan pembuatan vaksin. Hingga bulan Mei 2022 terdapat 16 vaksin yang tengah menjalani uji klinis fase I/II. Di antara vaksin HIV yang sudah pernah menjalani uji klinis fase III, hanya vaksin RV 144 yang memberikan hasil menjanjikan yakni efikasi mencapai 31,2%. Perkembangan vaksin HIV terus berlanjut untuk mendapatkan vaksin HIV yang aman dan efektif.